2019
DOI: 10.1016/j.ijmm.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of invasive and non-invasive group B Streptococcus circulating in Serbia

Abstract: Streptococcus agalactiae (group B Streptococcus, GBS) remains the leading cause of invasive diseases in neonates and an important cause of infections in the elderly. The aim of this study was to access the prevalence of GBS genito-rectal colonisation of pregnant women and to evaluate the genetic characteristics of invasive and non-invasive GBS isolates recovered throughout Serbia.A total of 432 GBS isolates were tested for antimicrobial susceptibility, capsular polysaccharide (CPS) types and the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
(42 reference statements)
4
25
3
1
Order By: Relevance
“…In our study, the GBS colonization level was found to be around 20% during the examined period. This value falls into the range of the colonization rates (i.e., from 6.5% to 36%) reported earlier for European countries [15,17], but it is somewhat higher than that reported recently in the neighboring country, Serbia (15%) [18]. At the same time, this relatively high colonization rate emphasizes the importance of the accurate GBS screening of pregnant women.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In our study, the GBS colonization level was found to be around 20% during the examined period. This value falls into the range of the colonization rates (i.e., from 6.5% to 36%) reported earlier for European countries [15,17], but it is somewhat higher than that reported recently in the neighboring country, Serbia (15%) [18]. At the same time, this relatively high colonization rate emphasizes the importance of the accurate GBS screening of pregnant women.…”
Section: Discussionsupporting
confidence: 47%
“…Our study also indicates a significant distribution of the ST-17 clone. Recently, Gajic et al [18] found this sequence type as the most common clone in Serbian samples. Moreover, the rate of erythromycin and clindamycin co-resistance was found to be extremely high among the ST-1 clones (52.1%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most of them were diagnosed with constitutive MLS B and ten times less with inducible MLS B . The constitutive MLS B mechanism was also the most commonly found mechanism of macrolide resistance by other authors in Poland [ 34 , 35 ], Serbia [ 30 ], Germany [ 36 ], and France [ 37 ]. Other groups of antibiotics were also assessed in this study.…”
Section: Discussionmentioning
confidence: 91%
“…During the last decades resistance to macrolides and lincosamides emerged. The percentages of strains resistant to erythromycin and clindamycin varied between European countries and were reported as 43.7% and 32.2% in Italy [ 17 ], 30.0% and 28.0% in Switzerland [ 29 ], 23.1% and 21.3% in Serbia [ 30 ], and 14.5% and 14.0% in Sweden [ 31 ]. Moreover, outside Europe, a worrying trend towards increasing resistance to these antibiotics group have been found, especially in China (78.6%–92.5% of strains resistant to erythromycin and 64.3%–87.5% resistant to clindamycin) [ 5 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%